Error Estimates for 1D Asymptotic Models in Coaxial Cables with Non-Homogeneous Cross-Section (Advances in Applied Mathematics and Mechanics, 2021)
This paper is the first contribution towards the rigorousjustification of asymptotic 1D models for thetime-domain simulation of the propagation of electromagneticwaves in coaxial cables. Our general objective is to derive errorestimates between the "exact" solution of the full 3D model and the"approximate" solution of the 1D model known as the Telegraphist's equation.